Bibliometric Analysis of the Journal of Global Postcolonial Studies, 1997-2024: Publication Trends and Citation Patterns - Mondal, Debdas (Information Research Communications, 2026)
Objectives/Purpose This study presents a comprehensive bibliometric analysis of the Journal of Global Postcolonial Studies covering the period from 1997 to 2024, to evaluate its publication trends, authorship patterns, thematic evolution, and citation impact. Methodology Using metadata extracted from the journal’s archives and citation counts obtained from Google Scholar, the analysis applies descriptive statistics and bibliometric tools such as Microsoft Excel, VOS viewer, and Bibliometrix to map the journal’s scholarly trajectory. Results The results reveal a steady increase in publication output, a predominance of single-authored contributions, and significant institutional and geographic diversity, with leading contributions from India, the United States, and the United Kingdom. Keyword analysis highlights dominant themes such as postcolonialism, identity, diaspora, hybridity, and colonial legacies, along with emerging areas including migration, memory, and globalisation. Citation analysis indicates rising academic influence, with several highly cited articles shaping the development of the field. Conclusion Overall, the study demonstrates that the Journal of Global Postcolonial Studies has played a vital role in advancing global postcolonial scholarship and continues to contribute significantly to the expansion of interdisciplinary research in the humanities.
Keywords: Bibliometrics; Citation Analysis; Journal Analysis; Postcolonial Studies; Publication Trends; Research Impact; Scholarly Communication; VOS viewer.